Healthcare‐associated pneumonia: A US disease or relevant to the Asia Pacific, too?. Issue 6 (25th July 2013) - Dobler, Claudia C.; Waterer, Grant
Abstract The term 'health care‐associated pneumonia' (HCAP) was introduced by the American Thoracic Society and the Infectious Diseases Society of America in 2005 to describe a distinct entity of pneumonia that resembles hospital‐acquired pneumonia rather than community‐acquired pneumonia (CAP) in terms of occurrence of drug‐resistant pathogens and mortality in patients that—while not hospitalized in the traditional sense—have been in recent contact with the health‐care system. It was proposed that HCAP should be treated empirically with therapy for drug‐resistant pathogens. Over the last few years, there has been increasing controversy over whether HCAP is a helpful definition, or leads to unnecessary and potentially problematic overtreatment. The term HCAP has been extensively criticized in Europe. While most studies have shown that HCAP is associated with more frequent drug‐resistant pathogens and higher mortality than CAP, there is no clear evidence that this is due to inappropriate antibiotic therapy. Therapy consistent with HCAP treatment guidelines has also not been found to improve mortality. Based on current evidence, we suggest broad‐spectrum antibiotic therapy to treat possible pathogens not usually covered in CAP be based on assessment of individual risk factors rather than applying a HCAP classification system in the Asia‐Pacific Region.